Recording your family history : a guide to preserving oral history with videotape, audiotape, suggested topics and questions, interview techniques - Fletcher, William P. (Dodd, Mead, 1986)
A program designed to help record the oral history of a relative or friend and preserve it on audio or video tape for future generations.